2023
DOI: 10.1098/rspb.2023.0196
|View full text |Cite
|
Sign up to set email alerts
|

When origin, reproduction ability and diet define the role of birds in invasions

Abstract: The ecological impacts of invasive alien species (IAS) are increasingly documented; however, they are usually studied through the lens of either the IAS or the affected species (IAS-threatened species). A clear understanding of how both protagonists of biological invasions are characterized is still lacking. We investigated the morphology, life history and ecology of birds involved in biological invasions. Evaluating the distribution of 450 IAS-threatened birds and 400 alien birds in a functional space, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Understanding why some exotic species become established in a new location while others fail remains a challenging question (Enders et al, 2020). Studies have shown that the success of exotic species depends on a combination of different factors involving propagule pressure, the biotic characteristics of the recipient ecosystem and exotic species traits (Allen et al, 2017; Bernery, Bellard, Courchamp, Brosse, & Leroy, 2022; Blackburn et al, 2009; Capellini et al, 2015; Marino & Bellard, 2023; Novoa et al, 2020). For instance, reptiles and amphibians established in exotic environments have larger or more frequent clutches compared with species that fail to establish (Allen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding why some exotic species become established in a new location while others fail remains a challenging question (Enders et al, 2020). Studies have shown that the success of exotic species depends on a combination of different factors involving propagule pressure, the biotic characteristics of the recipient ecosystem and exotic species traits (Allen et al, 2017; Bernery, Bellard, Courchamp, Brosse, & Leroy, 2022; Blackburn et al, 2009; Capellini et al, 2015; Marino & Bellard, 2023; Novoa et al, 2020). For instance, reptiles and amphibians established in exotic environments have larger or more frequent clutches compared with species that fail to establish (Allen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Exotic birds that are successfully established mostly present slow life‐history traits (e.g. large body mass and low brood value; Sol et al, 2012), while those with high ecological impacts have large clutch sizes (Marino & Bellard, 2023). In addition, exotic freshwater fish with a broad food spectrum have a greater chance of establishing than species with more specialized diets (Ruesink, 2005), although this varies with the stage of invasion (Bernery, Bellard, Courchamp, Brosse, Gozlan, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…I based this selection on previous evidence linking these traits to prey-predator relationships (Caron et al, 2022; Desjardins-Proulx et al, 2017; Gravel et al, 2013; Kopf et al, 2021; O’Connor et al, 2020) or linking them to domestic cat predation in particular (Woinarski et al, 2017). I sourced seven traits from two databases: body mass (continuous), tail length (continuous), hand wing index (continuous), trophic niche (categorical: granivore, vertivore, aquatic predator, invertivore, omnivore, nectarivore, aquatic herbivore, terrestrial herbivore, frugivore, scavenger) and primary lifestyle (categorical: insessorial, generalist, terrestrial, aerial, aquatic) from the AVONET database (Tobias et al 2022); and clutch size (numeric) from Marino & Bellard (2023). I obtained information about species’ habitat from the IUCN (2022) by adding eight dummy variables for each main habitat (wetlands, shrubland, grassland, wetlands, artificial/terrestrial, rocky, forest), where 0 indicates that the species is absent from this habitat and 1 else.…”
Section: Methodsmentioning
confidence: 99%